Formal training in two-dimensional standardized photographic documentation during residency in plastic surgery - Rafael Denadai; Alexandre Suguimoto; Enrico Ghizoni; Celso Luiz Buzzo; Cesar Augusto Raposo-Amaral; Cassio Eduardo Raposo-Amaral (Revista Brasileira de Cirurgia Plástica, 2018)
Introduction: Plastic surgery requires diverse skills, knowledge, and competencies, and its scope is broad and challenging. Thus, all plastic surgeons go through extensive education/training, which begins during residency and continues throughout their lives. This study aims to outline a formal training program in 2-dimensional standardized photographic documentation ("photodocumentation") to complement surgical and scientific training during residency in Plastic Surgery. Methods: The components (strategies, topics covered, skills acquisition, and feedback processes) of training in photodocumentation during residency in Plastic Surgery were detailed. Results: Topics in the photodocumentation training program included resident activities, interactions among residents, professional photographers, and surgeons/preceptors, studio settings, cameras, lenses, principles (exposure, aperture, speed, ISO, and depth of field), lighting, preparation and positioning of patients and the camera, photoshoot conditions, photo views, photo database, image formats, computerized photogrammetry, and ethical and medical-legal issues. Conclusion: Training in photodocumentation complements the arsenal of skills needed by residents in Plastic Surgery for continuing education, in order to better prepare them for future careers.